2021
DOI: 10.1021/acsomega.0c05690
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of “Chloropicolinate Amides and Urea Derivatives” as Novel Inhibitors for Mycobacterium tuberculosis

Abstract: A series of 30 novel diamino phenyl chloropicolinate fettered carboxamides, urea, and thiourea derivatives were synthesized by coupling of methyl 4-amino-6-(2-aminophenyl)-3-chloropyridine-2-carboxylate with different acid chlorides, urea, and thiourea moieties, respectively. All of these compounds were characterized by 1H and 13C nuclear magnetic resonance spectroscopy, CHN analysis, and high-resolution mass spectra for confirmation of the structures. Two compounds were also characterized by single-crystal X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…107 Rifampicin and isoniazid are the first-line treatment for tuberculosis. 109 The emergence of multidrug resistant (MDR) Mtb forces treatment with toxic second-line drugs. 110 MDR-TB can inhibit the conversion of macrophages to glycolysis by downregulating the mRNA levels of LDH, PFKFB3 and Aldoa in macrophages differentiated from mouse bone marrow cells, thus inhibiting the cell supernatant levels of IL-1β associated with NLRP3 inflammasomes.…”
Section: Tuberculosismentioning
confidence: 99%
“…107 Rifampicin and isoniazid are the first-line treatment for tuberculosis. 109 The emergence of multidrug resistant (MDR) Mtb forces treatment with toxic second-line drugs. 110 MDR-TB can inhibit the conversion of macrophages to glycolysis by downregulating the mRNA levels of LDH, PFKFB3 and Aldoa in macrophages differentiated from mouse bone marrow cells, thus inhibiting the cell supernatant levels of IL-1β associated with NLRP3 inflammasomes.…”
Section: Tuberculosismentioning
confidence: 99%
“…Rao et al . have reported methyl 4‐amino‐6‐(2‐aminophenyl)‐3‐chloropicolinate amide derivatives ( 22 , Figure 8) and related urea and thiourea derivatives with MIC of 6.96‐68.96 μM with less cytotoxicity against macrophages [46] . The present scaffold 22 have gained advantages of pharmacophoric features of isoniazid or ethionamide having anti‐mycobacterial potential and few other chloropicolinate amide containing herbicides having potential to reduce unwanted bacterial growth without affecting human immune system.…”
Section: Introductionmentioning
confidence: 91%
“…Rao et al have reported methyl 4-amino-6-(2-aminophenyl)-3chloropicolinate amide derivatives (22, Figure 8) and related urea and thiourea derivatives with MIC of 6.96-68.96 μM with less cytotoxicity against macrophages. [46] The present scaffold 22 have gained advantages of pharmacophoric features of isoniazid or ethionamide having anti-mycobacterial potential and few other chloropicolinate amide containing herbicides having potential to reduce unwanted bacterial growth without affecting human immune system. The molecular docking against MurB enzyme (PDB ID: 5JZX) revealed their strong ChemistrySelect binding against the proposed biological target, however they have not performed the in vitro target inhibitory study to confirm the mode of action of 22 against MurB enzyme.…”
Section: Pyridinementioning
confidence: 99%
“…The new approach to drug discovery is the incorporation of various biologically active molecules in a single hybrid framework may allow changes in the biological properties of the hybrid molecule when compared to the parent molecule [27] . In continuation of our ongoing interest, [15,16,23–25] in the present study, we are amalgamating the urea and thiourea precursors with pharmaceutical important Sacubitril moiety and further explored their anti‐TB activity.…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, urea and thiourea are, the more polar, metabolically stable important precursors and are also known to possess potent anti‐mycobacterial activity [11–16] . Several derivatives of these compounds have been potentially identified to possess potent antituberculosis activity in the literature [17,18] .…”
Section: Introductionmentioning
confidence: 99%